Efficacy of antioxidant intervention and exercise intervention for lipid peroxidation in dialysis patients: a meta-analysis - Yu, Mengyuan; Liu, Shengmao; Li, Jian; Ni, Ce; Li, Xinyang; Cui, Wenpeng (Frontiers in Medicine, 2025)
BackgroundLipid peroxidation is a major factor known to contribute to occurrence of cardiovascular events in dialysis patients. This study aims to investigate whether antioxidant interventions can improve lipid peroxidation damage in dialysis patients.MethodsA comprehensive search in PubMed, Embase, and the Cochrane Library was conducted to identify eligible randomized controlled trials (RCTs) up to June 2024. Endpoints of interest included biomarkers related to Lipid peroxidation. The results from eligible studies were performed using RevMan 5.3 and Stata17.0 software.ResultsA total of 25 RCTs were included, involving eight interventions such as vitamin C supplementation, vitamin E supplementation, vitamin E-coated dialyzer, ω-fatty acid supplementation, curcumin supplementation, pomegranate juice supplementation, exercise intervention, and multiple antioxidant interventions. Outcome indicators included malondialdehyde (MDA) and oxidized low-density lipoprotein (Ox-LDL). The meta-analysis revealed that vitamin E supplementation caused significant reductions in MDA (p = 0.01). Treatment with vitamin E-coated dialyzer markedly decreased MDA levels (p < 0.0001). Curcumin supplementation significantly reduced Ox-LDL levels (p = 0.03). Exercise intervention decreased MDA levels (p < 0.0001). Multiple antioxidant interventions significantly decreased MDA (p = 0.01).ConclusionSupplementation of vitamin E, vitamin E-coated dialyzer treatment, curcumin supplementation, exercise intervention, and multiple antioxidant interventions can effectively reduce the level of lipid peroxidation biomarkers in dialysis patients.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO (CRD42023455399).